Романы. Повесть. Рассказы. Эссе: 1946-1954 / [комментарии Г. Ю. Бергельсона] - Белль Генрих (1989)
Экземпляры: аб. (1990) / Инвентарный номер: 30517 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Б 43 / ГРНТИ: 17.82.30 / ББК: 84(4Гем)-4